2012
DOI: 10.1002/ibd.21929
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone and Colitis: Increased Mortality in Rodents and in Humans

Abstract: Background and Methods Crohn’s disease causes intestinal inflammation leading to intestinal fibrosis. Spironolactone is an anti-fibrotic medication commonly used in heart failure to reduce mortality. We examined whether spironolactone is anti-fibrotic in the context of intestinal inflammation. In vitro, spironolactone repressed fibrogenesis in TGFβ-stimulated human colonic myofibroblasts. However, spironolactone therapy significantly increased mortality in two rodent models of inflammation-induced intestinal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…In dog sepsis, specific MR agonists increased survival when given preventively [35] . It was also observed that mortality was enhanced by spironolactone during infectious colitis in two rodents model and in humans [36] . In neutrophils, functional MR was reported to mediate anti-inflammatory effects via inactivation of nuclear factor-kappa B (NF-κB); indeed aldosterone strongly diminished NF-κB dependant TNF-α production in IL-8 stimulated neutrophils, resulting in reduced neutrophil adhesion to endothelial cells [37] .…”
Section: Discussionmentioning
confidence: 92%
“…In dog sepsis, specific MR agonists increased survival when given preventively [35] . It was also observed that mortality was enhanced by spironolactone during infectious colitis in two rodents model and in humans [36] . In neutrophils, functional MR was reported to mediate anti-inflammatory effects via inactivation of nuclear factor-kappa B (NF-κB); indeed aldosterone strongly diminished NF-κB dependant TNF-α production in IL-8 stimulated neutrophils, resulting in reduced neutrophil adhesion to endothelial cells [37] .…”
Section: Discussionmentioning
confidence: 92%
“…Spironolactone is a competitive aldosterone receptor antagonist that is commonly used as an anti-fibrotic medication in heart patients, and has proven protective in several rodent models of fibrosis (Ersoy et al, 2007; Gullulu et al, 2006; Nishimura et al, 2008; Rajagopalan and Pitt, 2003). Previously, our group determined that spironolactone was anti-fibrotic in isolated human colonic myofibroblasts and repressed TGFβ-mediated induction of pro-fibrotic genes and proteins (Johnson et al, 2012a). To determine whether spironolactone could prevent TGFβ-induced fibrogenic gene and protein expression in HIOs, we analyzed the expression of fibrogenic genes and proteins in HIOs by qPCR and Western blot after 96 hours of co-treatment of various concentrations of spironolactone with 2 ng/mL TGFβ.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were serum-starved overnight before stimulation with 1 ng/mL of TGF-β as previously described. 18,38 To determine the effect of Rho/ ROCK or Rho/MRTF/SRF inhibitors, cells were cotreated with 1 ng/mL TGF-β and 1, 3, 10, 17.5, or 25 μM of inhibitors and incubated for 48 hours before harvest for molecular analysis. The media was replaced at 24 hours with fresh media containing TGF-β or TGF-β and inhibitors.…”
Section: Methodsmentioning
confidence: 99%